An Emergency Medicine Perspective for Non-Convulsive Status Epilepticus Patients: Intravenous Midazolam - Ramazan Güven; Mehmet Nuri Aydın; Eylem Kuday Kaykısız (Eurasian Journal of Emergency Medicine, 2017)

(untitled)
Non-convulsive status epilepticus (NCSE) characterized primarily by changes in consciousness in association with typical electroencephalography (EEG) changes is not very common; however, it is usually difficult to diagnose this SE type. NCSE should be one of the differential diagnoses for patients who present to the emergency department with impaired consciousness. There is no standard approach in the literature proposed by emergency physicians for NCSE patients. It is understood from current literature that intravenous (IV) diazepam is the most commonly used first-line therapy following the diagnosis with EEG. In the two case reports, we analyzed our approach for the patients with known refractory epilepsy who presented to the emergency department due to somnolence based on the preliminary diagnosis of NCSE. In this context, we concluded that IV midazolam was a fast and effective agent to terminate seizure of patients with known refractory epilepsy.